2006
DOI: 10.1103/physrevb.73.195415
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of Co-induced magic clusters grown onSi(111)(7×7): Scanning tunneling microscopy and spectroscopy and real-space multiple-scattering calculations

Abstract: The electronic structure of cobalt-induced magic clusters grown on Si͑111͒-͑7 ϫ 7͒ is investigated by scanning tunneling microscopy, scanning tunneling spectroscopy, and real-space multiple-scattering calculations. Topographical images of a half unit cell of Si͑111͒-͑7 ϫ 7͒ with the cluster acquired at low bias voltages of ±0.4 V show greatly reduced cluster heights; however, the heights of the corner adatoms are unchanged, indicative of the highly localized nature of the charge distribution. Spectroscopic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[1][2][3][4] In the past decade, self-assembled ordered metal nanoclusters with identical sizes have been successfully fabricated on Si͑111͒-͑7 ϫ 7͒ superlattice at the elevated substrate temperature. [5][6][7][8][9][10][11][12][13][14] The atomic structures and formation mechanism of these nanoclusters are the key concerns. Despite considerable efforts, many earlier works [15][16][17][18] could only assume the atomic structures of these clusters ambiguously due to the poor elemental specificity of scanning tunneling microscopy ͑STM͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In the past decade, self-assembled ordered metal nanoclusters with identical sizes have been successfully fabricated on Si͑111͒-͑7 ϫ 7͒ superlattice at the elevated substrate temperature. [5][6][7][8][9][10][11][12][13][14] The atomic structures and formation mechanism of these nanoclusters are the key concerns. Despite considerable efforts, many earlier works [15][16][17][18] could only assume the atomic structures of these clusters ambiguously due to the poor elemental specificity of scanning tunneling microscopy ͑STM͒.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by combining the STM image analysis and the theoretical simulation, the atomic structures have been determined for a number of clusters with elements such as univalent group I A metal ͑Na͒, 19,20 trivalent group III A metals ͑Al, Ga, and In͒, 5-9 tetravalent group IV A metal ͑Pb͒, 10 and 3d ferromagnetic group VIII metals ͑Co and Fe͒. [11][12][13] It has been found that metals in the same group tend to form a similar cluster structure and vice versa. In other words, the atomic structure of the nanocluster has a characteristic of the varying valence.…”
Section: Introductionmentioning
confidence: 99%
“…Such a charge transfer occurs because it can lower the total energy of the system. Self-assembled clusters of various metals formed on Si(111)-7 × 7, which have similar network as Ge clusters, have been reported [24,27,28,[90][91][92]. Several groups suggested that the interaction between the substrate and the metal clusters might play a role for the self-organization [24,27,28], and other researchers had emphasized the interaction between the clusters themselves [93].…”
Section: Evolution Of Hexagonal Ge Cluster Superlatticementioning
confidence: 87%
“…The clean Si(111)-7 × 7 surface is metallic [ 77 ], but the Si(111)-7 × 7-C 2 H 5 OH surface has a band gap of 2.2 V [ 64 ]. It is known that the atoms or atom cluster of Co, In, Ag, and Sn adsorbed on clean Si(111)-7 × 7 surface are non-metallic [ 63 , 70 , 78 , 79 ]. As shown in Figure 22 (a), 5 nm width Ag dots having 1–2 layers have a band gap of about 2.0 V, but the band gap of Ag dots becomes narrower when the dot has 3–5 layers and the Ag dots have more than five layers, are metallic as shown in Figure 22 (b) [ 71 ].…”
Section: Controlled Growth Of Nano-materials On Composite Surfacesmentioning
confidence: 99%